The effects of gingival blood flow on pulpal blood flow detection using ultrasound Doppler flowmetry: animal study - Dohyun Kim; Hyoung-Seok Ko; Soo-Yeon Park; Seung-Yeon Ryu; Sung-ho Park (Restorative Dentistry & Endodontics)
ObjectivesThis study evaluated the effect of adjacent gingival blood flow on detection of pulpal blood flow (PBF) using ultrasound Doppler flowmetry (UDF) through animal study.Materials and MethodsThe study included 36 right and left maxillary the third incisors and canines in 9 experimental dogs. The study included 2 main steps: In the first step, the pulse sound level (PSL) was recorded on the cervical part of each tooth without flap elevation (Group 1), with flap elevation (Group 2), and after it was repositioned in place (Group 3). In the second step, the PSL was recorded on the cervical part of each tooth (Group 4), after pulpotomy (Group 5), after partial pulp extirpation (Group 6), after complete extirpation (Group 7), and after canal filling (Group 8). In Groups 5–8, the study was performed with and without flap elevation in the left and right teeth, respectively. The PSL was graded as follows: 0, inaudible; 1, heard faintly; and 2, heard well. The difference between each group was analyzed using Friedman’s test with Wilcoxon signed-rank tests (α = 0.05).ResultsIn step 1, the PSL results were Group 1 > 2 and 3. In step 2, there was no significant difference between the groups when the flap was not elevated, while PSL results were Group 4 > 5 ≥ 6 and 7 ≥ 8 when the flap was elevated.ConclusionsPBF is affected by gingival blood flow when measured with UDF. UDF measurements require isolation of gingiva from the tooth.